Hydropower Infrastructure Performance after the 2015 Gorkha, Nepal, Earthquake Sequence. (December 2017) - Pehlivan, Menzer; Madugo, Christopher Madden; Macdonald, Amy; Rayamajhi, Deepak; Hashash, Youssef M. A.; Tiwari, Binod
Hydropower infrastructure, the primary source of electricity in Nepal, experienced severe damage following the 2015 Gorkha earthquake sequence, resulting in a 15% loss in the country's energy production. The performance of hydropower infrastructure during and after the sequence was one of the unique focuses of the Geotechnical Extreme Events Reconnaissance (GEER) study. The GEER team visited damaged hydropower projects along the Trishuli and Sunkoshi rivers by road and on foot, along with the ongoing 465-MW Upper Tamakoshi hydropower project by helicopter. The primary cause of damage to the hydropower infrastructure was landslide and rockfall debris falling on powerhouses, penstocks, and dam structures. Moreover, landslides blocked road access to many sites, delaying necessary repairs to damaged structures and resumption of power generation. Power production in Nepal before and after the 2015 Gorkha earthquake sequence, seismic performance of visited hydropower projects, and short- and long-term effects, together with residual risks for Nepal's hydro-power infrastructure, are discussed in this paper.